Actividades lúdicas y su incidencia en el aprendizaje de las matemáticas en estudiantes de quinto año EGB, de la Unidad Educativa Abdón Calderón Muñoz, Babahoyo, 2022 – 2023 - Iza López, Angélica Sofia (2023)
Playful activities play a fundamental role in the improvement of mathematics learning, including recreational practices, didactic materials, blackboard exercises and challenges that promote reasoning, the search for solutions and the active participation of all students, essential skills in both the academic and personal spheres. For this reason, the main purpose of this study is to establish how recreational activities affect the learning of mathematics in fifth grade students of the Abdón Calderón Muñoz Educational Unit, Babahoyo, 2022 - 2023. The methodology of this research has a quantitative approach, because a series of numerical data was collected and examined, a qualitative approach was also used to collect and analyze textual data, on the other hand, the type of research of this study was non-exploratory and explanatory. It is important to emphasize that the data obtained are the result of two research techniques, an interview with the fifth grade teacher and a survey of 37 students. The results showed that it is important to integrate frequently and effectively recreational games in the teaching of mathematics, with the purpose of increasing interest and motivation for learning; the data evidences that the effective implementation of this strategy provides a positive experience to the students of the Fifth year of EBG. Also, it was shown that the teacher plays an essential role in the design and planning of recreational practices, since he/she is in charge of identifying learning obstacles in the study of mathematics.